2023
DOI: 10.1021/acsnano.3c01405
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on Filament Growth Dynamics in Microstructure-Controlled Storage Media of Resistive Switching Memories

Abstract: The filament growth processes, crucial to the performance of nanodevices like resistive switching memories, have been widely investigated to realize the device optimization. With the combination of kinetic Monte Carlo (KMC) simulations and the restrictive percolation model, three different growth modes in electrochemical metallization (ECM) cells were dynamically reproduced, and an important parameter, the relative nucleation distance, was theoretically defined to measure different growth modes quantitatively;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 58 publications
(220 reference statements)
0
16
0
Order By: Relevance
“…Based on our previously developed KMC modeling, 10 which successfully reproduced three filament growth modes in the ECM cells observed in experiments, some modifications were made to mimic filament growth processes in ECM cells by insertion of an ion-blocking layer (IBL), a nanopore-containing graphene monolayer, between the anode and the dielectric layer as shown in Fig. 1a to illustrate the cooperative effect of the ion-blocking layer and the inhomogeneity of the dielectric layer: (1) the IBL was treated as 0.2 nm-thick inactive grids, and it keeps unchanged in the whole KMC simulations.…”
Section: Computational Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on our previously developed KMC modeling, 10 which successfully reproduced three filament growth modes in the ECM cells observed in experiments, some modifications were made to mimic filament growth processes in ECM cells by insertion of an ion-blocking layer (IBL), a nanopore-containing graphene monolayer, between the anode and the dielectric layer as shown in Fig. 1a to illustrate the cooperative effect of the ion-blocking layer and the inhomogeneity of the dielectric layer: (1) the IBL was treated as 0.2 nm-thick inactive grids, and it keeps unchanged in the whole KMC simulations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In our previous kinetic Monte Carlo (KMC) simulations, we found that the filament growth dynamics in active metal electrode/dielectric/inert metal electrode ECM cells can be well tuned by only changing the microstructures of dielectric layers with sufficient consideration of their inhomogeneity. 10 This nanomanipulation was not considered in the previous KMC simulations on CF growth in ECM cells, by using either two-dimensional (2D) grids 11,12 or three-dimensional (3D) grids. 13,14 We believe that the more complex nanomanipulation here by both introducing a nanopore-containing IBL and adopting the inhomogeneous RS layer in ECM cells can affect filament growth further to finally fulfill the memristor performance enhancement.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations